2001
DOI: 10.1038/sj.ejcn.1601187
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose supplementation with lycopene or β-carotene does not enhance cell-mediated immunity in healthy free-living elderly humans

Abstract: Objective: To assess the effects of supplementation with the carotenoids, b-carotene or lycopene, at levels achievable within a diet rich in fruit and vegetables, on immune function in a group of free-living healthy elderly. Design: A double-blind randomized placebo-controlled trial. T cell subsets and the expression of functionally associated cell surface molecules, quanti®ed by¯ow cytometry, and lectin-stimulated lymphocyte proliferation, were compared before and following the treatment period. Subjects: Fif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 40 publications
2
22
1
Order By: Relevance
“…The potential benefit of β-carotene in a model of allergic inflammation is less clear. β-Carotene has been shown to either have no effect [31][32][33][34][35][36] or lead to an increase [34,36,37] in circulating leukocyte and/or natural killer (NK) cell numbers. However, β-carotene has been shown to enhance NK cell function [38][39][40] and inhibit NF-κB activity in LPS-exposed cells [41].…”
Section: Discussionmentioning
confidence: 99%
“…The potential benefit of β-carotene in a model of allergic inflammation is less clear. β-Carotene has been shown to either have no effect [31][32][33][34][35][36] or lead to an increase [34,36,37] in circulating leukocyte and/or natural killer (NK) cell numbers. However, β-carotene has been shown to enhance NK cell function [38][39][40] and inhibit NF-κB activity in LPS-exposed cells [41].…”
Section: Discussionmentioning
confidence: 99%
“…All men were also given a standard multivitamin (1 tablet/day, Dixon/Akyma) and instructed to refrain from any other types of vitamin or mineral supplements during the three months of intervention. The fish oil and lycopene doses were selected based on the minimal and maximal range at which previous clinical trials had observed physiologic effects and no toxicity for lycopene [14], [15], [16], [17], [18] [19] [7], [20] and fish oil supplementation [21], [22], [23], [24], [25], [26], [27]. The intervention duration of three months was chosen based on previous studies that reported on gene expression changes within three months [15], [21], [28]; and based on consultation with local prostate cancer advocates and support groups who advised that most men would prefer not to stop other supplements for more than three-months.…”
Section: Methodsmentioning
confidence: 99%
“…115,117,133 Only one RCT, conducted in healthy older men and women (N ϭ 20), has reported an effect of ␤-carotene supplementation (30 -60 mg/d) on lymphocyte counts; CD4 cell counts increased from baseline after 2 months of supplementation (Table 3; please go to www.ilsi.org/ Publications/NutritionReviews/). 122 Other RCTs did not find significant effects of carotenoid supplementation at doses ranging from 15 to 300 mg on the proportions or absolute counts of circulating total T-cells, 114,[118][119][120][121] CD3, 118,119,122,126 CD4, 114,[118][119][120][121]126 or CD8 cells, 114,[118][119][120]122,126 cytotoxic T-cells, 119,121 or memory T-cells. 119,121 Of the four RCTs that have examined changes in the CD4/CD8 ratio, 114,118,121 only one observed a statistically significant effect of carotenoid supplementation 121 (Table 3; please go to www.ilsi.org/ Publications/NutritionReviews/).…”
Section: Lymphocyte Subpopulationsmentioning
confidence: 98%
“…27 In nonsmoking older men and women from Ireland, low-dose carotenoid supplementation for 3 months (8.2 mg/d ␤-carotene or 13.3 mg/d lycopene) was not associated with changes in total leukocytes counts compared with placebo 114 (Table 3; please go to www.ilsi.org/Publications/NutritionReviews/). The participants were not followed after the end of the supplementation period.…”
Section: Distribution Of Cell Typesmentioning
confidence: 99%